2008
DOI: 10.1111/j.1600-0846.2008.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lotioned disposable handkerchiefs on skin barrier recovery after tape stripping

Abstract: The controlled pre-damaged forearm method with tape stripping appears to be a suitable model to study the effects of repetitive wiping on irritated skin with disposable handkerchiefs of different quality. More specifically, the model seems applicable to mimic the nasolabial skin damage observed during a common cold associated with frequent use of disposable handkerchiefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Measurement of transepidermal water loss (TEWL) and erythema are other non‐invasive techniques used in the tape‐stripping model to study skin barrier function indirectly . Erythema is primarily a subjective method, which is therefore a limiting measure in skin damage research.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of transepidermal water loss (TEWL) and erythema are other non‐invasive techniques used in the tape‐stripping model to study skin barrier function indirectly . Erythema is primarily a subjective method, which is therefore a limiting measure in skin damage research.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from a number of studies provide support for the contribution of individual constituents to the efficacy observed. De Paepe et al24 reported that lotioned handkerchiefs containing fatty alcohols and mineral oils helped prevent skin damage caused by the wiping on skin-stripped forearms of volunteers. Additionally, topical application of a combination nanoparticle product (trehalose, ceramide, and cholesterol) increased skin capacitance by up to 40% and decreased TEWL by 15% compared with placebo 25.…”
Section: Discussionmentioning
confidence: 99%